Analysis of the Application of the Principle of Proportionality Article 31 of Law Number 1 of 1974 concerning Marriage in the Division of Rights and Obligations of Husband and Wife - Nurillah, Juliana; Putra, Muh. Yunan; Jainuddin, Jainuddin (International Journal of Nusantara Islam, 2025)
The principle of proportionality is a fundamental principle in law which emphasizes the balance between rights and obligations, and is relevant to apply in the context of husband and wife relationships. The provisions of Article 31 of Law Number 1 of 1974 concerning Marriage still base the division of roles between husband and wife on a traditional structure, which in practice is often not in harmony with contemporary social dynamics. This study uses a normative juridical approach and is analyzed qualitatively through a literature study and review of a number of Religious Court decisions. The results of the analysis show that an imbalance in the implementation of roles between husband and wife is the dominant factor in divorce cases. Although the principle of proportionality has not been explicitly accommodated in positive legal norms, its application is starting to appear in the legal considerations of several judges as a form of substantive justice. Therefore, mainstreaming the principle of proportionality in the formation of national law and family justice practices is an urgent need to realize justice, equal roles and family resilience in Islamic society in Indonesia.